2019
DOI: 10.1002/aenm.201901935
|View full text |Cite
|
Sign up to set email alerts
|

Polysulfide Confinement and Highly Efficient Conversion on Hierarchical Mesoporous Carbon Nanosheets for Li–S Batteries

Abstract: performance of Li-S batteries is still restricted by poor conductivity of sulfur itself and discharge products (Li 2 S/Li 2 S 2 ), which makes hard conversion of sulfur. Additionally, the common shuttle effect of intermediate polysulfide also leads to an obvious capacity loss during charging and discharging. [10][11][12][13][14][15] Thus, new strategies are urgent in addressing the problems of high-capacity sulfur cathodes for Li-S batteries.To design high-performance cathode, dispersing nanostructured sulfur … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(63 citation statements)
references
References 54 publications
(115 reference statements)
1
62
0
Order By: Relevance
“…To increase the affinity of carbon hosts on polysulfide species, a class of guest species, such as single atoms, metal clusters, or metal compounds, are introduced into the mesoporous carbon materials, which can provide chemisorption interaction and then can further reduce the shuttle effect of polysulfides. [41,45] The lithium-air batteries (LABs) provide a higher theoretical energy density up to ≈3460 Wh kg −1 compared with other rechargeable energy storage devices. [46,47] The main challenges associated with LABs are to accommodate the deposition insulating Li 2 O 2 particles generated during discharge and to accelerate the formation of original reagents (Li + O 2 ) from the sluggish backreaction during charge.…”
Section: Rechargeable Batteriesmentioning
confidence: 99%
“…To increase the affinity of carbon hosts on polysulfide species, a class of guest species, such as single atoms, metal clusters, or metal compounds, are introduced into the mesoporous carbon materials, which can provide chemisorption interaction and then can further reduce the shuttle effect of polysulfides. [41,45] The lithium-air batteries (LABs) provide a higher theoretical energy density up to ≈3460 Wh kg −1 compared with other rechargeable energy storage devices. [46,47] The main challenges associated with LABs are to accommodate the deposition insulating Li 2 O 2 particles generated during discharge and to accelerate the formation of original reagents (Li + O 2 ) from the sluggish backreaction during charge.…”
Section: Rechargeable Batteriesmentioning
confidence: 99%
“…Interestingly, only one broad cathodic peak around 2.35 V can be detected in subsequent two cycles; it is reported that the conversion of sulfur to Li 2 S, also called “quasi‐solid‐state” becomes the main reaction mechanism . Comparatively, when the S/MC 3 was tested in ether‐based electrolyte, it is possible to observe three cathodic peaks at 2.30, 2.02, and 1.88 V in the first cycle (Figure B), which presents different electrochemical redox behaviors as compared with other sulfur/carbon or sulfur/metal compounds based cathodes . The peaks at 2.3 and 2.02 V can also be caused by the two‐step reduction reactions of the elemental sulfur with metallic lithium, respectively forming high‐order soluble polysulfides (Li 2 S x , 4 ≤ x ≤ 8) and low‐order polysulfides (Li 2 S x , 2 ≤ x < 4).…”
Section: Resultsmentioning
confidence: 94%
“…40 Comparatively, when the S/MC 3 was tested in ether-based electrolyte, it is possible to observe three cathodic peaks at 2.30, 2.02, and 1.88 V in the first cycle ( Figure 5B), which presents different electrochemical redox behaviors as compared with other sulfur/carbon or sulfur/metal compounds based cathodes. [16][17][18][19][20] The peaks at 2.3 and 2.02 V can also be caused by the two-step reduction reactions of the elemental sulfur with metallic lithium, respectively forming high-order soluble polysulfides (Li 2 S x , 4 ≤ x ≤ 8) and low-order polysulfides (Li 2 S x , 2 ≤ x < 4). Also, the peak at 1.88 V might be the slow conversion of the low-order polysulfides to insoluble Li 2 S 2 and Li 2 S, 41 which could be attributed to slow lithium ion migration in the inner pore of the MC, as well as limited transformation dynamics from the liquid-phase to insulating solid-phase.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations